STRATEGI DAN PROSPEK PEGADAIAN SYARIAH BAGI PENINGKATAN EKONOMI USAHA MIKRO KECIL MENENGAH - R. ajeng Entaresmen; Nuraini Chaniago (Media Ekonomi, 2022)
The purpose of this study was to determine the sharia pawnshop strategy for improving the economy of micro, small and medium enterprises at PT. Pegadaian Syariah X in Tangerang, Banten, to find out the prospect analysis of Pegadaian Syariah for improving the economy of micro and small businesses at PT. Pegadaian Syariah X in Tangerang, Banten. This method is a qualitative research method is a research method based on the philosophy of post-positivism, used to examine the condition of natural objects, where the researcher is the key instrument, the sampling of data sources is carried out purposively and snowball, the research technique of collecting data is tri-angulation (combined). ), data analysis is inductive or qualitative using SWOT analysis. The results of the study show that Pegadaian is present as an alternative solution to the problem of limited capital, especially for Micro, Small and Medium Enterprises (MSMEs). In general, MSMEs really hope for financing opportunities that have easy access, light and easy requirements, fast acquisition times, and light installments. they can provide. In accordance with the facts on the ground related to support for national economic growth